A Study on the Creation of Chinese Contemporary Dance Inspired by the Qiang Ethnic Dance Culture in Northern Sichuan - Shan, Wang; Natayakulwong, Sirimongkol (Journal for Developing the Social and Community, 2025)
Background and Aims: The Qiang ethnic minority of Northern Sichuan, China, possesses a rich tradition of dance practices that embody spiritual, ritualistic, and social meanings. However, these traditions remain underrepresented in contemporary artistic discourse. This study aims to investigate the traditional dance forms of the Qiang people and reinterpret them through the creation of a contemporary Chinese dance work, XiangYun, employing participatory dance culture management principles to ensure cultural sustainability and ethical engagement. Methodology: The research adopted a qualitative, practice-led approach integrating ethnographic fieldwork, semi-structured interviews, and collaborative choreographic workshops. Thematic content analysis was employed to interpret cultural and choreographic data, while descriptive statistics were used to analyze audience feedback. Community members were actively engaged as co-creators throughout the artistic development process. Results: The study identified three principal Qiang dance forms: Wu, Sacrifice, and Guozhuang, each with distinct ritualistic and communal functions. The co-creation process led to the development of XiangYun, incorporating traditional motifs into contemporary aesthetics. Audience evaluations indicated strong perceptions of cultural authenticity (95%) and emotional engagement (90%), affirming the effectiveness of participatory methodologies in sustaining intangible cultural heritage. Conclusion: The findings demonstrate that participatory, practice-led approaches can foster culturally sensitive and innovative reinterpretations of traditional dance. Collaborative engagement with community members not only enhances artistic authenticity but also supports the sustainable transmission of cultural knowledge. This research highlights the potential of participatory frameworks to bridge tradition and innovation within contemporary dance practices.